Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology - Roháček, Jindřich; Tóthová, Andrea (European Journal of Taxonomy, 2021)
A new species of Anthomyzidae (Diptera), viz., Mumetopia interfeles Roháček sp. nov. (both sexes), is described from Chile, based on a large series collected from a small grassy area (consisting of a non-native species, Hordeum murinum L.) among houses in the city of Valparaíso. Its systematic affiliation, phylogenetic relationships, and biology are discussed. Cases of mass occurrence of adult Anthomyzidae, particularly those in anthropogenic habitats, are reviewed and general features of them discussed. A phylogenetic hypothesis is proposed for the relationships of the new species and the Chamaebosca group of genera within Anthomyzidae (64 species in dataset), based on Bayesian inference and maximum likelihood analyses of seven DNA markers (12S, 16S, 28S, COI, COII, CytB, ITS2). Taxonomic limits of the genus Mumetopia Melander, 1913 are discussed. Based on a new molecular hypothesis and a previous cladistic analysis of morphological data (Roháček & Barber 2009), a broadened, better-supported concept of Mumetopia (s. str.) is proposed to include M. interfeles sp. nov. (and its unnamed relatives) and externally aberrant, undescribed species endemic to the Juan Fernández Islands. Apart from Anthomyzidae (M. interfeles sp. nov. only), the community of Diptera associated with H. murinum was dominated by phytophagous Chloropidae: Ceratobarys sacculicornis (Enderlein, 1911) occurred in extremely high numbers similar to those of M. interfeles sp. nov., while the less abundant Opetiophora sp. represents the first record of the genus from South America.